2008
DOI: 10.1016/j.pain.2007.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Novel histamine H3 receptor antagonists GSK189254 and GSK334429 are efficacious in surgically-induced and virally-induced rat models of neuropathic pain

Abstract: Several studies have implicated a potential role for histamine H(3) receptors in pain processing, although the data are somewhat conflicting. In the present study we investigated the effects of the novel potent and highly selective H(3) receptor antagonists GSK189254 (6-[(3-cyclobutyl-2,3,4,5-tetrahydro-1H-3-benzazepin-7-yl)oxy]-N-methyl-3-pyridinecarboxamide hydrochloride) and GSK334429 (1-(1-methylethyl)-4-([1-[6-(trifluoromethyl)-3-pyridinyl]-4-piperidinyl]carbonyl)hexahydro-1H-1,4-diazepine) in two rat mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
75
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 39 publications
4
75
1
3
Order By: Relevance
“…Radioligand binding (Pollard et al, 1993;Medhurst et al, 2008), immunohistochemistry (Chazot et al, 2001), and in situ hybridization studies show the existence of H 3 Rs throughout the CNS (Pillot et al, 2002). The highest densities of binding sites were seen in the striatum, cerebral cortex, and olfactory tubercles.…”
Section: Histamine and H 3 Rs In The Nervous Systemmentioning
confidence: 98%
See 1 more Smart Citation
“…Radioligand binding (Pollard et al, 1993;Medhurst et al, 2008), immunohistochemistry (Chazot et al, 2001), and in situ hybridization studies show the existence of H 3 Rs throughout the CNS (Pillot et al, 2002). The highest densities of binding sites were seen in the striatum, cerebral cortex, and olfactory tubercles.…”
Section: Histamine and H 3 Rs In The Nervous Systemmentioning
confidence: 98%
“…Early measurements of inflammatory peptide release suggested that H 3 Rs are present on sensory nerves (Delaunois et al, 1995;Ohkubo et al, 1995;Imamura et al, 1996;Rouleau et al, 1997;Poveda et al, 2006), but the localization of H 3 Rs within the peripheral nervous system and spinal cord (Pollard et al, 1993;HĂ©ron et al, 2001;Medhurst et al, 2008) was only recently confirmed by immunohistochemistry (Cannon et al, 2007a). In rat and mouse skin, H 3 R-like immunoreactivity (H 3 RLI) was absent in all of the thin-caliber epidermal and superficial dermal innervation, but present in a subset of thin-caliber fibers associated with arterioles in the deep dermis (Fig.…”
Section: Histamine and H 3 Rs In The Nervous Systemmentioning
confidence: 99%
“…164) In contrast to the latter, GSK334429 is a less rigidized 1,4-diazepane possessing comparable properties to that of GSK189254. It is active in attention and cognition models but what is more important, both, GSK189254 and GSK334429, have recently shown to be efficacious in models of neuropathic pain 165) pointing out a possible additive indication for these short-acting and poor brain penetrating ligands as H 3 R modulates pain reception in the dorsal horn and spinal cord 48) (Fig. 7, Tables 1, 2).…”
Section: )mentioning
confidence: 99%
“…However, recent studies on selective H 3 R inverse agonists, GSK189254 and GSK334429, demonstrate efficacy in models of acute and neuropathic pain. 164,165) In this context, autoradiography studies with [ 3 H]GSK189254 show a distinct H 3 R expression pattern in the dorsal horn of human and rat spinal cord and in human dorsal root ganglion. These areas are generally associated with neurochemical processes on nociceptive conduction by cross-linking peripheral and central pathways of sensitisation.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation